An Outline of Christianity;: the story of our civilization ... (Bethlehem Publishers, Inc., 1926)
v. 1. The birth of Christianity.--v. 2. The builders of the church.--v. 3. The rise of the modern churches.--v. 4. Christianity and modern thought.--v. 5. Christianity today and tomorrow.